Impact Of COVID – 19 On The Outcomes Among Patients With Chronic Liver Disease Along Comorbidities - A Prospective Cross-Sectional Study (Journal of Pharmaceutical Negative Results, 2022)
Chronic liver disease and cirrhosis are associated with immune dysregulation and might increase the risk of acquiring COVID-19 and developing more severe outcomes of it. In a Prospective Observational study of patients with chronic liver disease and cirrhosis, we investigated the association between liver disease and COVID-19. We assessed the impact of COVID-19infectionondiseaseseverityandthecourseofliverdisease. We included all patients with chronic liver disease and a positive RT-PCR test for SARS-CoV-2 between March 2021 to June 2021. There were 261 patients with chronic liver disease and COVID-19 in the study. Sixty-four (24.2%) patients had cirrhosis. People with cirrhosis were more likely to require hospitalization than patients with chronic liver disease (71.8% versus16.2%, p < 0:001) and more likely to be admitted to an intensive care unit (7.8% versus 3.6%, p = 0:005) and had higher rates of mortality (18.7% versus 1.5%, p = 0:001). In our study age, gender, and comorbidities, cirrhosis remained an independent predictor of severe COVID-19. Of hospitalized patients with cirrhosis, 41% experienced a worsening of their liver disease during their COVID-19 infection. Patients with chronic liver disease, especially those with cirrhosis, are at major risk of a severe COVID-19 disease course and higher mortality.